Drug Injection to Sites other than Arm: A Study of Iranian Heroin Injectors - Karimi, Mehrdad; Ghaheri, Hafez; Assari, Shervin; Moghani Lankarani, Reza; Moghani Lankarani, Maryam; Rafiey, Hassan; Narenjiha, Hooman; Ahmadi, Khodabakhsh; Tavakoli, Mahmood; Jafari, Firoozeh (Frontiers in Psychiatry, 2014)
For almost all injecting drug users (IDUs), the first injection is done to the arm. Years after in their injection career, they shift to using other sites for intravenous access. Although injection to sites other than arm is considered as a risky behavior, literature is poor regarding this behavior. We aimed to determine the prevalence and associated factors of using intravenous (IV) access points other than arm among a national sample of IDUs in Iran. In a secondary analysis of the national drug dependence survey in 2007, we enrolled all 863 IDUs with at least once daily heroin injections. Data on socio-demographics, drug use data and injection related behavior entered to a backward logistic regression to determine the predictors of our main outcome which was injection to any IV access points other than arm. From all participants, 54.8% reported current injection in sites other than arm. Injection sites were femoral venous sinus (17.0%), groin (14.5%), neck (11.5%), other sites (3.0%), or missing (8.8%). Logistic regression revealed that living alone (OR=1.789, 95% CI=1.218 to 2.629), being Sonni (OR=3.475, 95% CI=1.775 to 6.801), Having higher family income (OR=1.002, 95% CI=1.001 to 1.003), higher age at first drug use (OR=1.039, 95% CI=1.009 to 1.069), more injection duration (OR=1.071, 95% CI=1.041 to 1.102), and more injection frequency (OR=1.255, 95% CI=1.072 to 1.471) were associated with higher likelihood of use of IV access points other than arm. Use of the other sites than arm for IV injection shows an attachment to some socio-demographics, drug use data, and injection related characteristics which can be used by policy makers in harm reduction planning.